2013
DOI: 10.1074/jbc.m113.464123
|View full text |Cite
|
Sign up to set email alerts
|

A Secondary Structural Transition in the C-helix Promotes Gating of Cyclic Nucleotide-regulated Ion Channels

Abstract: Background: Cyclic nucleotide-regulated channels are involved in sensory transduction and repetitive electrical activity. Results: Transition metal ion FRET and electrophysiology demonstrated a coil-to-helix transition within the ligand binding domain. Conclusion: Agonist binding stabilized the structure of the C-helix, triggering channel gating. Significance: This transition is important for ion channel activation and may be necessary for the activation of other cyclic nucleotide-regulated proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 46 publications
5
42
0
Order By: Relevance
“…The ligand-induced movement of the C-helix is widely thought to initiate the conformational changes that lead to opening of the channel pore, but the structural evidence in support of this hypothesis is equivocal (10,(24)(25)(26)(27)(28)(29). The crystal structure of the HCN2 carboxyl-terminal region in the absence of ligand shows little difference from the cyclic nucleotide-bound structure (12).…”
mentioning
confidence: 93%
“…The ligand-induced movement of the C-helix is widely thought to initiate the conformational changes that lead to opening of the channel pore, but the structural evidence in support of this hypothesis is equivocal (10,(24)(25)(26)(27)(28)(29). The crystal structure of the HCN2 carboxyl-terminal region in the absence of ligand shows little difference from the cyclic nucleotide-bound structure (12).…”
mentioning
confidence: 93%
“…In addition to these initial structural insights about possible conformational changes of the mHCN2 CNBD upon ligandbinding, extensive structural analysis with transition metal ion FRET experiments support the 'coil-to-helix' transition of helix αF′ and a change in the length of helix αC upon ligand-binding (Taraska et al, 2009;Puljung and Zagotta, 2013). Furthermore, in intact CNGA1 channels, homologous to HCN channels, it was shown that stabilization of helix αC promoted channel opening by metal coordination by a pair of histidine residues (Puljung and Zagotta, 2013). In the same study, transition metal ion FRET results suggest movement of the N-terminal region of helix αC closer to the β roll core of the CNBD upon cyclic nucleotide binding.…”
Section: Structure Of Hcn2 Cnbd In the Ligand-free Statementioning
confidence: 99%
“…Minor structural differences include the overall α-helical content caused by the absence of helix αF′ and the shortening of helix αC (by five residues) in the apo-state. However, crystal packing interactions in the region of helix αC or putative ligand replacement by bromide ions located in the binding pocket may have forced the conformation of helix αC in the apo-state structure, and therefore this structure may not represent the actual apo-state conformation in solution (Taraska et al, 2009;Puljung and Zagotta, 2013). In addition to these initial structural insights about possible conformational changes of the mHCN2 CNBD upon ligandbinding, extensive structural analysis with transition metal ion FRET experiments support the 'coil-to-helix' transition of helix αF′ and a change in the length of helix αC upon ligand-binding (Taraska et al, 2009;Puljung and Zagotta, 2013).…”
Section: Structure Of Hcn2 Cnbd In the Ligand-free Statementioning
confidence: 99%
See 2 more Smart Citations